“Deadly”, “fierce”, “shameful”: notions of antiretroviral therapy, stigma and masculinities intersecting men’s life-course in Blantyre, Malawi - Berner-Rodoreda, Astrid; Ngwira, Esther; Alhassan, Yussif; Chione, Boniface; Dambe, Rosalia; Bärnighausen, Till; Phiri, Sam; Taegtmeyer, Miriam; Neuhann, Florian (BMC public health, 2021)
Stigma and masculinity represent persistent barriers in delivering successful HIV interventions to men. Our study examined community perceptions of HIV and anti-retroviral therapy (ART) and their implications for men on ART across the life course in Blantyre, Malawi.